Studies on Effects of Polymeric Films in Packaging Grapes - Deshpande, S D; Shukla, B D; Dhingra, D (Journal of Agricultural Engineering, 2002)
Two polymeric films were used for packaging of grapes for short-term storage under ambient conditions, protected from direct light. The films used were low density polyethylene (LDPE) of thickness 25m, 50m and 75m and polypropylene (PP) of 25m and 38m. At the end of 7th day of packaging, packaged grapes had no colour change and no mould growth/fungal attack was observed. At the end of 10th day, samples in all bags turned brownish and mould growth was visible. The mass loss from the non-packaged grapes was 5.71 % after 5 days and 9.87% after 7 days as compared to 3.07% after 5 days and 5.91 % after 7 days storage for the grapes packaged in 25m PP films. Sensory evaluation studies indicated acceptability of packaged grapes upto 7 days of storage.